Social Media and Its Impact on Students’ Writing Skills - Hashim, Harwati; Md Yunus, Melor; Shazana M. Ibrahim, Nur; Elmira Jeri, Ivy; Afifie Mohamad Sukr, Muhammad; Syahirah Nazor Ilahi, Noor; Afif Nor Hassim, Muhammad (International Journal of Engineering and Technology, 2018)
Nowadays, social media such as Facebook, Twitter, Instagram, and WhatsApp are very popular among the young generations and they are easily influenced by these technologies. However, there are negative influences of using social media towards the language acquisition of the young generations.  The aim of this paper is to identify positive and negative impacts of social media on students writing skills.  To achieve the aim of the study, primary research was conducted using questionnaires which were distributed among 88 secondary school students at an academy in a state in Malaysia. The questionnaires were used to collect quantitative. Data were then analysed and reported in tables using frequencies and percentages.   The findings showed that there the students’ writing skills was impacted by the use of social media.